2015
DOI: 10.1128/iai.00887-15
|View full text |Cite
|
Sign up to set email alerts
|

Vigilant Keratinocytes Trigger Pathogen-Associated Molecular Pattern Signaling in Response to Streptococcal M1 Protein

Abstract: The human skin exerts many functions in order to maintain its barrier integrity and protect the host from invading microorganisms. One such pathogen is Streptococcus pyogenes, which can cause a variety of superficial skin wounds that may eventually progress into invasive deep soft tissue infections. Here we show that keratinocytes recognize soluble M1 protein, a streptococcal virulence factor, as a pathogen-associated molecular pattern to release alarming inflammatory responses. We found that this interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 54 publications
4
40
0
Order By: Relevance
“…We hypothesize that in the latter case, macrophages are intrinsically stimulated by cellular processes such as metabolic activation elicited by the thioglycollate pre-treatment in our in vivo experiments, or alternatively that M1 may activate host-derived pro-inflammatory factors facilitating signal 1 priming. The later mechanism is consistent with recent studies, which have shown that keratinocytes recognize soluble M1 as a PAMP to release interleukin-8, growth-related oncogene-alpha, migration inhibitory factor, and other inflammatory response alarms 37 . Another study reported that M1 protein can synergize with heparin-binding protein to interact with TLR2 on monocytes and promote release of IL-1β and IL-6 38 , which differs somewhat from our findings showing no effect of M1 protein on IL-6 production in vitro or in vivo .…”
Section: Discussionsupporting
confidence: 91%
“…We hypothesize that in the latter case, macrophages are intrinsically stimulated by cellular processes such as metabolic activation elicited by the thioglycollate pre-treatment in our in vivo experiments, or alternatively that M1 may activate host-derived pro-inflammatory factors facilitating signal 1 priming. The later mechanism is consistent with recent studies, which have shown that keratinocytes recognize soluble M1 as a PAMP to release interleukin-8, growth-related oncogene-alpha, migration inhibitory factor, and other inflammatory response alarms 37 . Another study reported that M1 protein can synergize with heparin-binding protein to interact with TLR2 on monocytes and promote release of IL-1β and IL-6 38 , which differs somewhat from our findings showing no effect of M1 protein on IL-6 production in vitro or in vivo .…”
Section: Discussionsupporting
confidence: 91%
“…This could be explained by two possible reasons. First, the chitosan‐based hydrogels were able to kill bacteria, inhibiting the overactivation of the inflammatory response induced by pathogen‐associated molecular patterns . Second, they could regulate macrophages to be M2 phenotype through the activation of the p‐STAT6 signaling pathway.…”
Section: Physicochemical Properties Of Chitosan‐based Hydrogels and Tmentioning
confidence: 99%
“…TGF‐β1 also regulates the expression of extracellular matrix proteins, including fibronectin and αβ integrins, and TGF‐β1 signaling has been shown to enhance GAS invasion of epithelial cells, suggesting that it may play a role in promoting bacterial colonization. In response to GAS infection, epithelial cells also secrete neutrophil chemoattractants, such as IL‐8, with this process likely to be an important protective mechanism elicited by epithelial cells during GAS pharyngitis …”
Section: Innate Immune Response To Gas Pharyngitismentioning
confidence: 99%